How Molecular Epidemiology Can Affect Tuberculosis Control in the Middle East Countries: A Systematic Review and Meta-Analysis - Asgharzadeh, Mohammad; Rashedi, Jalil; Poor, Behroz M.; kafil, Hossein Samadi; Zadeh, Hossein Moharram; Ahmadpour, Ehsan (Infectious Disorders - Drug Targets, 2021)
Background: Nowadays, due to the incidence of specific strains of Mycobacterium tuberculosis and also an increase in the rate of drug resistant-TB, the mortality rate has been increased by this disease. The identification of common strains in the region, as well as the sources of transmission, is essential to control the disease, which is possible by using molecular epidemiology. Objectives: In this survey, the studies utilizing the spoligotyping method in Muslim Middle East countries are reviewed to determine their role in the control of TB. Methods: All studies conducted from 2005 to June 2016 were considered systematically in three electronic databases out of which 23 studies were finally selected. Results: The average rate of clustering was 84% and the rate of recent transmission varied from 21.7% to 92.4%. The incidence of Beijing strains has been found to be rising in the abovementioned countries. In Iran and Saudi Arabia known as immigration and labour-hosting countries, respectively, rapid transmittable and drug-resistant Beijing strains were higher than those in other Muslim Middle East countries. Conclusion: Considering the incidence of highly virulent strains, due to the increase in immigration and people infected with HIV, tuberculosis, especially drug-resistant form, careful monitoring is needed.
Keywords: Beijing